Remote cerebellar hemorrhage with acute hydrocephalus after supratentorial surgery - Diop, Sylvain; Borius, Pierre-Yves; Degos, Vincent (Journal of Emergency and Critical Care Medicine; Vol 3 (September 2019): Journal of Emergency and Critical Care Medicine, 2019)
We report the case of a 57-year-old man without previous medical history undergoing left frontotemporal meningioma surgery (Figure 1). The neurosurgical procedure was performed under general anesthesia using a target-controlled infusion of remifentanil and propofol. Intra-operative course went well without hemodynamic instability or surgical complication. In early post-operative period, our patient presented no sign of awakening.